Identity processes and musicians during the COVID-19 pandemic. (December 2022) - Breakwell, Glynis M; Jaspal, Rusi
Musicians, both professional and amateur creators of music, faced economic, social, and psychological hardship during the pandemic. In this article, we use identity process theory from social psychology to interpret the potential impact of the COVID-19 pandemic on identity processes among musicians, including the significance of identity resilience and identity threat to their experience, and the strategies that may be employed in response to possible threats to identity. First, we provide a brief overview of empirical research into identity and well-being among musicians during the pandemic, which has shown the potential for identity threat and the multitude of coping strategies deployed by musicians during this period, most notably the move to virtual settings. We exemplify the theoretical observations made regarding identity processes and coping through three case studies focusing on quite different strategies musicians used to deal with identity threat during the 2020–2021 COVID-19 lockdowns. Awareness of the risks of identity threat and the variety of coping strategies that they can deploy against it could be valuable to musicians and others in the creative industries facing future societal upheavals. In crises, musicians can use music to create coping strategies both for themselves and to support others.